Human Tumor-Infiltrating Myeloid Cells: Phenotypic and Functional Diversity - Elliott, Louise A.; Doherty, Glen A.; Sheahan, Kieran; Ryan, Elizabeth J. (Frontiers in Immunology, 2017)
Our current understanding of human tumor resident myeloid cells is, for the most part, based on a large body of work in murine models or studies enumerating myeloid cells in patient tumor samples using immunohistochemistry (IHC). This has led to the establishment of the theory that, by and large, tumor resident myeloid cells are either ‘pro-tumor’ M2 macrophages or myeloid derived suppressor cells (MDSC). This concept has accelerated our understanding of myeloid cells in tumor progression and enabled the elucidation of many key regulatory mechanisms involved in cell recruitment, polarization and activation. On the other hand, this paradigm does not embrace the complexity of the tumor resident myeloid cell phenotype (IHC can only measure 1 or 2 markers per sample) and their possible divergent function in the hostile tumor microenvironment (TME). Here we examine the criteria that define human tumor infiltrating myeloid cell subsets and provide a comprehensive and critical review of human myeloid cell nomenclature in cancer. We also highlight new evidence characterizing their contribution to cancer pathogenesis based on evidence derived from clinical studies drawing comparisons with murine studies where necessary. We then review the mechanisms in which myeloid cells are regulated by tumors in humans. We then review the mechanisms in which myeloid cells are regulated by tumors in humans and how these are being targeted therapeutically.